2015
DOI: 10.1093/imaman/dpv002
|View full text |Cite
|
Sign up to set email alerts
|

Passive portfolio management over a finite horizon with a target liquidation value under transaction costs and solvency constraints

Abstract: We consider a passive investor who divides his capital between two assets: a risk-free money market instrument and an index fund, or ETF, tracking a broad market index. We model the evolution of the market index by a lognormal diffusion. The agent faces both fixed and proportional transaction costs and solvency constraints. The objective is to maximize the expected utility from the portfolio liquidation at a fixed horizon but if the portfolio reaches a pre-set target value then the position in the risky asset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Because of their nonlinearity and the degeneration of coefficients, HJB equations do not always have smooth solutions that are defined in a classical sense, while they admit solutions with lower regularity called viscosity solutions . Due to their rich mathematical properties, HJB equations and viscosity solutions have been analyzed from both analytical and numerical viewpoints . To our knowledge, PV systems have not been mathematically analyzed from the viewpoint of stochastic control and viscosity solutions, although they are potential mathematical tools for efficiently analyzing the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their nonlinearity and the degeneration of coefficients, HJB equations do not always have smooth solutions that are defined in a classical sense, while they admit solutions with lower regularity called viscosity solutions . Due to their rich mathematical properties, HJB equations and viscosity solutions have been analyzed from both analytical and numerical viewpoints . To our knowledge, PV systems have not been mathematically analyzed from the viewpoint of stochastic control and viscosity solutions, although they are potential mathematical tools for efficiently analyzing the systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the problem can be formulated as a stochastic impulse control problem [34][35]. There exist many stochastic impulse control models ranging from the exactly solvable [36], semi-analytical [37], and more complex models [38]. Most of them are based on the complete information assumption that the decision-maker who controls the system can continuously receive the complete information of its dynamics.…”
Section: Mathematical Backgroundmentioning
confidence: 99%
“…They demonstrated how to best adjust the portfolio so as to maximize an terminal utility function. Further studies along this line can be found in (Baccarin and Marazzina 2016) in which they considered a related problem with solvency constraints. They were able to establish the existence of an impulse policy and provided a numerical method.…”
Section: Introductionmentioning
confidence: 99%